2017
DOI: 10.1590/2359-3997000000287
|View full text |Cite
|
Sign up to set email alerts
|

Is fibroblast growth factor 23 a new cardiovascular risk marker in gestational diabetes?

Abstract: Objective: This study was designed to compare the serum levels of fibroblast growth factor 23 (FGF23) among patients with gestational diabetes mellitus (GDM) and healthy pregnant women, and to evaluate the association between hormonal and metabolic parameters. Subjects and methods: A total of 82 pregnant women were consecutively enrolled in the study. Of these, 46 were diagnosed as having GDM; the remaining 36 healthy pregnant women served as controls in a cross-sectional study design. The womens' ages ranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…It also participates in cardiovascular disturbances, including atherosclerosis and left ventricular hypertrophy [137, 138]. Notably, FGF-23 estimated adverse cardiovascular outcomes in women with T2DM [139], and also, high levels of FGF-23 (and low of adiponectin) diagnosed GDM at the 3rd trimester [140] (Table 4). Placenta-secreted factors…”
Section: Prospective Diagnostic and Predictive Markers For Gdm With Amentioning
confidence: 99%
“…It also participates in cardiovascular disturbances, including atherosclerosis and left ventricular hypertrophy [137, 138]. Notably, FGF-23 estimated adverse cardiovascular outcomes in women with T2DM [139], and also, high levels of FGF-23 (and low of adiponectin) diagnosed GDM at the 3rd trimester [140] (Table 4). Placenta-secreted factors…”
Section: Prospective Diagnostic and Predictive Markers For Gdm With Amentioning
confidence: 99%
“…FGF-23 requires a cofactor known as α-Klotho, protects the heart, for activation of FGF signaling. [33] Increased FGF-23 levels were observed in patients with gestational DM [34] and FGF-23 levels are associated with bone mineral density and preclinical vascular disease in patients Type 2 DM. [35] Ito et al [36] reported that FGF-23 levels were decreased in patients with acromegaly after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are focused on blood glucose monitoring for the management of GDM [72][73][74], and not on the prediction of post load glycemia as an early detection or alternative screening tool for this pregnancy disorder. Furthermore, although some of them evaluate the correlation between different variables and fasting glycemia [75][76][77], postprandial glycemia [78], glucose challenge test (GCT) post load glycemia [79,80] and OGTT post load glycemia [81][82][83], they don't test their predictive performance through error metrics like RMSE and RE. To our knowledge, this is the first study that introduces and properly assesses ML models to predict OGTT post load glycemia so as to make the early detection and screening of GDM independent of the diagnostic criteria.…”
Section: Plos Onementioning
confidence: 99%